System Reliability Modeling and Analysis of Distributed Networks. (31st January 2022) - Wei, Guanghui
Abstract : The reliability of distributed network is researched by establishing one set of effective modeling, analysis, evaluation, and optimization method theory, which is a hot research area in the distributed network system field. The phased analysis method is utilized to study the reliability of the distributed network including the analysis and definition of the distributed network on the basis of studying its operational process. Meanwhile, task request, task scheduling, and execution phase will be also studied, and the establishment of reliability mathematical model of distributed network will be discussed to provide actual reference significance for the design of the distributed network system.